Facial palsy as a manifestation of early neuroborreliosis (clinical case) - I.M. Poiasnyk (Medičnì Perspektivi)
Lyme borreliosis is a tick-borne transmitted infectious disease caused by the spirochete Borrelia burgdorferi sensu lato and spread by the bite of ticks of the genus Ixodes. Lyme neuroborreliosis is a clinical manifestation of Lyme borreliosis, which affects the central nervous system and peripheral nervous system in up to 15% of the affected patients. Nerve structures are affected by spirochetes both in acute and late phase of the disease. The clinical course of neuroborreliosis is highly variable. Although at least 80% of European patients present with facial nerve palsy and radiculitis, symptoms of neuroborreliosis may be quite unspecific or even mimic other neurological diseases. Idiopathic peripheral facial palsy has long been considered as the most common cause of prosopoparesis, but modern diagnosis significantly narrow the range of cases of unknown genesis. Neuroborreliosis is difficult to diagnose, especially when prosopoparesis is the only clinical manifestation, so practitioners should be mindful of possible etiology to avoid misdiagnosis. The article presents a clinical case of early neuroborreliosis in a woman of 57 years who manifested with peripheral facial palsy. The author describes in detail the course of the disease (the appearance of new symptoms on the background of standard medical therapy (poor response), the presence of additional criteria (erythema migrans, lymphocytoma (rarely), arthralgia), diagnosis (specific immunological examination of blood to Borrelia burgdorferi sensu lato). Antibiotic therapy made it possible to achieve complete recovery of facial nerve function and avoid future complications.